Implementasi MBKM Praktek Pencatatan Dan Penginputan Pada PT Intercon Terminal Indonesia - Adinda Labiba Ufairah Financy; Daffa Rahmadani; R.M Rum Hendarmin; Lukita Tripermata (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The Field Work Practice Program is one of the programs to support aspects of the expertise of every tertiary student. Field Work Practice is a form of direct activity in the world of work. This program is expected to increase knowledge about activities that occur within a company and can also support theoretical knowledge from lecture material. Field Work Practices are carried out at PT Intercon Terminal Indonesia with the hope of obtaining information and knowledge in the field directly according to the chosen field. The author records data and inputs data to the company's website based on transactions that occur in the company sent via company email. In addition, after participating in Field Work Practice activities, you can also add insight into how the actual accounting cycle in a company is. Provide new experiences for students about how the world of work actually is, interact with many people, how to discuss to solve problems, and also provide knowledge that is very useful for students when they are already in the world of work